Open BIM-based LCA of HVAC and circularity assess-ment using the Madaster platform - Theißen, Sebastian; Pelzer, Björn; Höper, Jannick; Drzymalla, Jan; Claudius, Frank; Bergmann, Patrick; Meins-Becker, Anica (CLIMA 2022 conference, 2022)
In Life Cycle Assessments (LCA) of buildings and circularity assessment, Heating Ven-tilation and Air-Conditioning (HVAC) systems are almost completely ignored due to the lack of regulation requirements, simplified consideration in green building certification and high com-plexity. Therefore, there is a lack of relevant information that enables a comprehensive whole building LCA and a circularity assessment of materials in HVAC. Using a digital Material Passport (MP) for buildings enables combining whole building LCA with qualitative and quantitative as-sessments of circularity. The open Building Information Modeling (BIM) method and the open data exchange format Industry Foundation Classes (IFC) offer a high potential for the efficient creation and management of a MP, as data can be integrated, linked and exchanged in 3D models with a high degree of semantics. This work analyses the life cycle assessment and circularity of two design variants of Ventilation and Air-Conditioning (VAC) systems of an office building within an open BIM-based process. Thereby, the embodied carbon of the VAC design variants was ana-lyzed within an open BIM-based LCA. As a second step, the VAC models were assessed regarding their circularity using the Madaster Circularity Indicator (MCI) and detachability index within the Madaster platform as a case study. The results show that the impact of VAC materials is very im-portant to consider within a whole building LCA, as VAC cause high material-related embodied impacts. In addition, the circularity assessment, using MCI and Detachability index, shows that the reduction of material mass does not influence the assessment. Instead, Design for Disassem-bly (DfD) turns out as a very important factor, which can also provide information for a more realistic assignment of end-of-life scenarios, effecting LCA results interpretation in the future. However, therefore various competencies in planning, data modelling and sustainability assess-ment need to be more connected. The open BIM approach already offers the tools to make this more efficient and automated. The research shows advantages and obstacles of open BIM based LCA and circularity assessment of HVAC and provides insights for further research regarding a more holistic assessment of buildings.